Antithrombotics increase bleeding after endoscopic submucosal dissection for gastric cancer: Nationwide propensity score analysis. Issue 5 (19th October 2021) - Nagami, Yasuaki; Hatta, Waku; Tsuji, Yosuke; Yoshio, Toshiyuki; Kakushima, Naomi; Hoteya, Shu; Tsuji, Shigetsugu; Fukunaga, Shusei; Hikichi, Takuto; Kobayashi, Masakuni; Morita, Yoshinori; Sumiyoshi, Tetsuya; et al.
Abstract : Objectives: Post‐operative bleeding is the most common adverse event in endoscopic submucosal dissection (ESD) for early gastric cancer (EGC). Patients taking antithrombotic agents has increased. We evaluated the influence of antithrombotic agents on delayed bleeding in ESD for EGC. Methods: This was a post hoc analysis of nationwide, multicenter, retrospective cohort study in Japan. Altogether, 11, 452 patients who underwent ESD for EGC in 33 institutions between November 2013 and October 2016 were enrolled. The primary outcome was the incidence of delayed bleeding in patients with or without antithrombotic agents. The secondary outcome was the incidence of delayed bleeding in those who took each antithrombotic agent and the cessation status of its use compared with each matched pair of patients. We used propensity matching and inverse probability of treatment weighting (IPTW) analyses. Results: There were 1353 matched pairs of patients. The incidence of delayed bleeding was 2.8% and 10.7% in those without and with antithrombotic agents, respectively (odds ratio [OR] 4.15, 95% confidence interval [CI] 2.88–5.99; P  < 0.001). The IPTW analysis showed similar results (OR 4.21, 95% CI 3.48–5.08; P  < 0.001). Antiplatelets, anticoagulants, and their combination increased such incidence. Heparin bridging therapy had high OR (8.80), and the continuation (OR 3.46) and cessation (OR 2.95) of antithrombotic agent use had similar risk. Conclusions: Antithrombotic agents increased the incidence of delayed bleeding in patients who underwent ESD for EGC. Continuing antithrombotics may be more appropriate than heparin bridging therapy.